Jaime Alvar - José María Blázquez (eds.) Héroes y antihéroes de la Antigüedad Clásica. Madrid, Edic. Cátedra, 1997, 332 pp. I.S.B.N.: 84-376-1505-4. - Monti, Gabriela A. (2000)
Fil: Monti, Gabriela A..